Education, Patriarchy, and Time Allocations of Married Couples - Leena Bhattacharya; Arthur Van Soest (Global Labor Organization (GLO), 2025)
How married couples allocate their time across activities has been studied in developed countries, but remains an open question in many developing countries. We pool the 2019 and 2024 waves of the India Time Use Survey (TUS), the two most recent nationally representative surveys, to analyze the time spent on paid work, household production, child care, and several other activities. We focus on the role of spouses' relative education level - which has been seen as a measure of within-household bargaining power - as well as each partner's own education level and a measure of patriarchy in the state. We find that, compared to women with lower or the same education level, women with higher education than their husbands are more likely to participate in and spend more time on paid work, at the cost of time spent on household production, leisure, childcare, and sleep. Surprisingly, men with more educated wives also spend somewhat more time on paid work than other men. In addition, they more often engage in household production and childcare activities, which leads to reduced intrahousehold inequality in time spent on unpaid activities. Combined with the relations between time use and wives' and husbands' own education or patriarchy, our results suggest that the impact of relative education is more complex than its role for intrahousehold bargaining power would suggest.
Keywords: J22; J16; 330; relative education; time allocation; gender; bargaining power